Measurement the Mentality of Residents of the New Districts and Planned in Relation with the Guality of Life Components (Case Study: Jahed neighborhood of Mashhad) - Fatemeh Mohamad Niaye Qaraee; Marzieh Teimouri; MohamadAli Khanizadeh (جغرافیا و توسعه, 2017)
Paying attention only to the growth of cities and to avoid developing developmental approaches toward cities has led to the emergence of macrocosmic phenomena, which has a direct impact on the quality of life in cities. A remarkable point in dealing with quality of life is to consider it in all dimensions (subjective and objective), so that it can be comprehensively evaluated. Therefore, the present article aims to analyze and evaluate the quality of life (two objective and subjective dimensions) in urban planning areas seeking to improve the quality of life in these neighborhoods by increasing the environmental components.The study area is Jahed Shahr  in 12th district of Mashhad. The criteria and indicators for the objective and subjective quality of life in four levels have been developed hierarchically. The method used is objective and applied in terms of descriptive-analytical method.Data were collected using library and field studies. Using the Cochran formula, 372 individuals were selected as sample size and questionnaires distributed as simply randomized . Data analysis was done using SPSS and AMOS software. Results: The quality of life in Jahed Shahr  Neighborhood was assessed  moderate to weak level  (only in the good transportation sector) and the objective quality of life is moderately upward (only in the components of social security and leisure).